The moderating effect of institutional quality on the relationship between structural change and CO2 emissions in emerging economies - Daghbagi Hamrouni; Radhouane Hasni; Imen Ouerghi (Environmental and Sustainability Indicators)
Structural change, which has led to significant progress in social and human development, as evidenced by the progress of the Emerging and Growth Leading Economies (EAGLEs), also has a direct impact on environmental quality. This transformation is largely influenced by the quality of institutions, which may therefore moderate the relationship between structural change and environmental quality. This study examines the impact of structural change and institutional quality on CO2 emissions in these economies from 2000 to 2021, including the effect of their interaction. Using the ARDL-PMG model, control variables such as GDP, energy consumption and urbanization are included to account for the specific characteristics of these economies. The results show that GDP, energy consumption and urbanization contribute to higher emissions, while structural change and institutional quality directly reduce CO2 emissions. Moreover, their interaction creates a combined effect that amplifies this reduction, highlighting the synergy between structural transformation and the institutional framework, while emphasizing the need for coordinated action to better target environmental policies. Policy recommendations are derived from these empirical findings.